PROSES MANAJEMEN DALAM PRODUKSI SENI PERTUNJUKAN - Dadang Suganda (Paraguna, 2016)
Production  Management of Performing Arts is an activity to organize and coordinate the use of human,   material,  financial,   and information resources. This activity is conducted effectively and efficiently to create and enlarge benefits for the performing arts produced.  Management   of thePerforming Arts  can be considered as  the process of achieving  a variety ofresources to produce multipurpose performing arts. It  is also the process ofreaching the goals and  objectives of the organization,  both  commercially,socially,  as well  as potentially to maintain  the existence of performance artitself.